A comparison of sleeping patterns with brainwaves of music preference based on gender among undergraduate students in Universiti Malaysia Sarawak (UNIMAS) - Isabel, Paramasivam (Universiti Malaysia Sarawak (UNIMAS), 2015)
The brainwaves pattern of male and female vary to a certain extend especially in terms of musical preferences and sleeping patterns. This research aims to compare the sleeping patterns between male and female respondents from both musical and non-musical background in relation to the brainwave patterns based on their musical preferences using quantitative electroencephalogram (qEEG). EEG brain signals were captured from 4 male and 4 female respondents of Universiti Malaysia Sarawak (UNIMAS) based on the music listening tasks administered. The data collected were then filtered and later classified into four frequency bands. It was observed that, in average Delta wave is the highest brainwave present at the frontal cortex in all respondents during the music listening tasks. On the other hand, comparing frequency bands to that of gender, female undergraduates had higher Beta wave as compared to males. Moreover, the most prominent sleeping pattern was identified among the 8 respondents as well. This research highlights that most undergraduates in UNIMAS are of Evening Type sleeping pattern with music preferences towards Upbeat and Conventional factor (e.g. country, gospel, oldies, pop, religious and soundtracks).